To be or not to be a systems thinker: Do professional characteristics influence how students acquire systems-thinking skills? - Miller, Anat Nissel; Kordova, Sigal; Grinshpoun, Tal; Shoval, Shraga (Frontiers in Education, 2023)
The importance of finding systems thinkers is growing as the need for systems thinking increases. Systems thinkers can see a system as a whole made up of elements that interact with each other, identify the interrelationships within the system, and understand the impact of components on each other and the complete system, which facilitates learning what affects the system. This article examines factors that influence a person’s ability to become a systems thinker, by analyzing the systems thinking capabilities of population groups with different characteristics: working engineering students, full-time engineering students, social workers, and educators in a technological college. These groups have different characteristics related to employment, level of professional skills, degree of familiarity with their working environment and level hierarchy of the organization. A questionnaire that examined systems thinking capabilities was distributed to these groups before and after a learning process about systems thinking, to see if and how various aspects of their systems thinking changed as a result of this learning. The results show differences in various aspects of systems thinking in each group following the learning process and a linkage between different group characteristics and various aspects of systems thinking. Knowing that the varied characteristics of different groups influence their ability to become systems thinkers can help us understand how to train systems thinkers. Specific training processes must be adapted to groups with different characteristics.